The arrival - Tan, Shaun (London : Hodder Children's Books, 2007)
In this wordless graphic novel, a man leaves his homeland and sets off for a new country, where he must build a new life for himself and his family.
School Library Journal starred
Wilson's Junior High School
Wilson's Senior High School
5-8.
5-8
Keywords: Emigration and immigration -- Comic books, strips, etc -- Juvenile fiction; Immigrants -- Comic books, strips, etc -- Juvenile fiction; Stories without words; Cartoons and comics; Emigration and immigration -- Fiction; Immigrants -- Fiction; Stories without words; Comic books, strips, etc; Graphic novels; Immigrants -- Comic books, strips, etc -- Fiction; Immigration and emigration -- Comic books, strips, etc -- Fiction; Stories without words; Graphic novels